Selective Recognition of Myoglobin in Biological Samples Using Molecularly Imprinted Polymer-Based Affinity Traps - Rüstem Keçili (International Journal of Analytical Chemistry)
The current work demonstrates the design, characterization, and preparation of molecularly imprinted microspheres for the selective detection of myoglobin in serum samples. The suspension polymerization approach was applied for the preparation of myoglobin imprinted microspheres. For this purpose, N-methacryloylamino folic acid-Nd3+ (MAFol- Nd3+) was chosen as the complex functional monomer. The optimization studies were performed changing the medium pH, temperature, and myoglobin concentration. pH 7.0 was determined as the optimum value where the prepared imprinted microspheres displayed maximum binding for myoglobin. The maximum binding capacity was achieved as 623 mgg−1. In addition, the selectivity studies were conducted. The results confirmed that the imprinted microspheres showed great selectivity towards myoglobin in the existence of hemoglobin, cytochrome c, and lysozyme which were chosen as potentially competing proteins.